(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2025)
Behavioral therapist’s research and intervention practices involve taking assumptions about cause and behavior, because theoretical confusion results in confusion in practice too. The text presents different thought traditions that culminated in different definitions of causality throughout history, including scholastic doctrine, the scientific method and the experimental analysis of behavior. For Scholasticism, the cause is remote, immanent in the effect and efficient. It contrasts with the scientific method inaugurated by Galileo Galilei, which points out the contingencies of nature in the search for knowledge, rejects subjective aspects, and values observation and measurement. The objective of this text is to evaluate Behavior Analysis’ conception of cause, formulated mainly by B. F. Skinner, as a scientific proposal, with implications for behavior analysts. The authors suggest some conceptions of causality should be adopted in detriment of others, that can be abandoned.